Perancangan Sistem Inventori Barang pada Kedai Kopi Kopiah Berbasis Web - Agung Wijoyo; Indra Cahya Firdaus; Sofyan Mufti Presetiyo (Gema Wiralodra, 2022)
The development of technology is growing speedily, so the utilization of knowledge system technology is incredibly helpful for firms that require correct, quick and careful data. Kedai Kopi Kopiah may be a look engaged in food and beverages. This shop, in managing inventory, remains in an exceedingly typical method, specifically recording it in an exceedingly book. ranging from recording incoming merchandise, outgoing merchandise, to creating reports still mistreatment typical strategies. so it will cause a delay within the explore for merchandise and hamper in creating reports. so to beat this, a processed system is required. this {method} is intended with the UML (Unified technique Language) method. Programming languages mistreatment markup language, PHP, and MySQL databases. supported downside analysis, the results obtained area unit that this inventory system will offer data that's accessed by admins, super admins, and suppliers. Admin will add, change, and delete item knowledge, class knowledge, incoming merchandise and outgoing merchandise. Meanwhile, to feature users, purchase of products and print reports will solely be done by super admin. The provider will receive notification of the acquisition of products created by the super admin. This inventory system was created to form it easier for firms to manage stock things and supply quicker data. This application will perform knowledge search mechanically, record incoming and outgoing merchandise, and may generate reports of incoming and outgoing merchandise.